District Health System in Health Care Service for Diabetes and Hypertension Patients: A Case Study in Phana District, Amnat Charoen Province. - หน่อแก้ว อัญชลี; แสงสว่าง ภูเบศร์ (Journal of Preventive Medicine Association of Thailand, 2018)
The objective of this study was designed to determine the District Health System in Essential care for Diabetes and Hypertension patients in Phana District, Amnat Charoen Province during October 2013 to September 2014. Materials and methods: The questionnaires were used to collect data from 31 Districts Health System committees. Data analysis were used Descriptive Statistics. Results: Phana District was used the District Health System follows the principles 1.) District-Level Cooperation. The committee covers 3 sections as local government sector, local administrative organization and public sector. Including specific working teams such as non-communicable disease team has cross functional integration team. 2.) Appreciation and Quality between the service recipients and service providers. The results of satisfaction showed that most of the participants had moderate level (69.6% of service recipients and 66.7% 0f Phana District Health Workers) 3.) Resources sharing and personnel development, based on requirement from personnel in each area. For personal development were learning base on area context merge with routine to research strategies. 4.) Selection of health problems for essential care at Phana district, Diabetes and Hypertension have chosen as one district-one problem. 5.) Community participation, Health networking potential development training was occur, budget supporting by local administrative organization. For diabetes and hypertension patients’ health care was applied self-efficacy and social support theories. This study found that the number of patients with uncontrolled diabetes and hypertension were decreased after end of studies. Furthermore, this program was expand cover Phana district, the patients participate in community activities, health care in their family and themselves. Health facilities were developing the health system management to reach a standard both of operation and policy. Conclusions: The study suggested that the government authorities should add up the role of District Health System Committee from another sections. Moreover, glorification for another health system networking should be providing. Essential care service should be push forward to the district issue. Thus, all sectors in local level will acknowledge the policy management and will cooperate and participate in the workgroup and could be sustainable.